Developing a Coffee-Based Export Village: Strengthening Quality, Branding, and Market Access for Community Empowerment - Novi Wulandari Widiyanti; Agung Budi Sulistiyo; Bayu Aprillianto; Imamatin Listya Putri; Muhammad Miqdad (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Coffee is one of Indonesia's primary export commodities that contributes substantially to regional economic growth. Karangpring Village in Jember Regency holds considerable potential for producing high-quality coffee, yet faces persistent challenges in quality assurance, business legality, and international market access. This community service program aimed to strengthen the capacity of local farmers and micro, small, and medium enterprises (MSMEs) through halal certification training, product diversification, branding development, and export literacy. Activities were conducted through structured workshops, technical mentoring, and digital marketing facilitation in collaboration with local institutions. Program outcomes included greater awareness of business legality requirements, the creation of coffee-based product innovations such as coffee bakpia, and the institutional development of BUMDes as a production and marketing coordinator. Halal certification raised consumer confidence and broadened export market opportunities. This initiative offers a replicable model of sustainable, export-oriented community development in rural Indonesia.